THE INFLUENCE OF WORK MOTIVATION, JOB SATISFACTION, AND WORK DISCIPLINE, ON EMPLOYEE PERFORMANCE INDEPENDENT ELECTION COMMISSION (KIP) CITY LHOKSEUMAWE AND ACEH UTARA - Nadila Yusrina; Em. Yusuf Iis; Adnan; Likdanawati (RADJA PUBLIKA, 2025)
This research aims to determine the influence of the work motivation, job satisfaction, work discipline on employee performance at Komisi Independen Pemilihan (KIP) of Lhokseumawe City and Aceh Utara. The independent variables in this research are work motivation, job satisfaction, and work discipline, meanwhile the dependent variable is employee performance. This type of research uses quantitative methods and data collection uses a questionnaire containing questions and statements by distributing them to the employees concerned at Komisi Independen Pemilihan (KIP) of Lhokseumawe City and Aceh Utara. By giving scores using a Likert scale. This research was conducted with a population of 68 employees, where sampling used the saturated sample method. This research uses multiple linear regression analysis with the SPSS (Statistical Program For Social Science) program. . The results of this research indicate that the work motivation has a positive and significant effect on employee performance at Komisi Independen Pemilihan (KIP) of Lhokseumawe City and Aceh Utara, job satisfaction has a positive effect on employee performance at Komisi Independen Pemilihan (KIP) of Lhokseumawe City and Aceh Utara, work discipline has a positive and significant effect on employee performance at Komisi Independen Pemilihan (KIP) of Lhokseumawe City and Aceh Utara.